KESIAPAN APARAT BIROKRASI MENUJU PARADIGMA GLOBAL PELAYANAN PUBLIK - Bambang Wicaksono (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2002)
The issue of public service provision has become more serious in Indonesia in line with increasing public awareness of the need for customer-oriented public service delivery. The institutional capacity preparations and good quality human resources within the bureaucracy confines should back up endeavors in the direction of instituting a new public service delivery paradigm, which among other things, should uphold the sovereignty of the user. Bureaucracy, as a public service institution, must be equipped with the ability to adopt the concept of an adaptive organization, which is a public service delivery institution always sensitive to any changes in the needs and environment of service users the people.